Experimental and theoretical study to improve the performance of splits in Iraq - Jasim, Qusay Kamil; Jassim, Najim Abd (Journal of engineering sciences and information technology, 2022)
In air conditioning cooling systems, especially in regions with extremely hot weather, reducing power consumption and improving performance are key concerns. In the summer, the system’s efficiency drastically declines and its use of electricity significantly rises. This article analysis an experimental and theoretical study to improve the performance of evaporative condensers used in air conditioning using evaporative cooled air. The paper mainly focuses on the energy consumption of residential cooling systems and their performance improvement in Iraq. The result shows that when the air entering the condenser is cooled via evaporative cooling, the average compressor work consumption is lowered by 8.2% as a result of the 5% drop in condenser pressure. The highest temperature at the condenser’s air outlet surface was lowered by 5 C when evaporative-cooled condensers were utilized, and power consumption was found to be decreased by 13.7 to 58%.